Climate anxiety impairs sustained attention: objective evidence of a cognitive cost - Denkova, Ekaterina; Tardibuono, Taylor K.; Tsukahara, Jason S.; Zanesco, Anthony P.; Jha, Amishi P. (Frontiers in Psychology, 2025)
IntroductionAs climate anxiety rises globally, it may influence how individuals cognitively engage with the climate crisis. Although cognitive functioning is a key component of climate anxiety, its association with objectively measurable cognitive performance impairment remains unclear. This study examines whether individual differences in climate anxiety correspond with performance on a task measuring sustained attention.MethodsA total of 182 undergraduate students completed self-report measures of climate anxiety, personal climate change experience, and general anxiety and depression. In addition, they completed the Sustained Attention to Response Task (SART), which measures attentional performance through accuracy and response time variability.ResultsGreater climate anxiety was associated with reduced SART accuracy (r = −0.310, p < 0.001) and greater response time variability (r = 0.188, p = 0.024). Consistent with prior research, climate anxiety also correlated with personal experience of climate change and higher levels of anxiety and depression. However, personal experience with climate change as well as anxiety and depression were not significantly related to SART outcomes.DiscussionResults show that greater climate anxiety is associated with reduced attentional task performance, independent of climate change experience or general psychological distress. Given the central role of attention in decision-making and action-planning, these findings underscore how this cognitive vulnerability may pose a critical barrier to adaptive engagement and effective climate action. The findings also highlight the need for research on approaches to bolster sustained attention as we face growing climate anxiety in a warming world.